SGLT-2 inhibition by empagliflozin exerts neutral effects on experimental arterial thrombosis in a murine model of low-grade inflammation. (3rd October 2022) - Liberale, L; Kraler, S; Puspitasari, Y; Bonetti, N; Akhmedov, A; Ministrini, S; Montecucco, F; Marx, N; Lehrke, M; Hartmann, N U K; Beer, J H; Paneni, F; et al.
Abstract: Introduction: Low-grade inflammation couples dysmetabolic states to insulin resistance and atherosclerotic cardiovascular disease (ASCVD). Selective sodium-glucose co-transporter 2 (SGLT-2) inhibition by empagliflozin improves clinical outcomes in patients with ASCVD independently of glucose-lowering. Yet, its mechanism of action remains largely undetermined. Purpose: We aimed to test whether empagliflozin affects arterial thrombus formation in baseline conditions or low-grade inflammation, a systemic milieu shared among patients with ASCVD. Methods: Sixteen-week-old C57BL/6 mice were randomly assigned to acute administration of empagliflozin (25 mg/kg BW) or vehicle, of which a subgroup was pre-treated biweekly over 4 weeks with super-low-dose lipopolysaccharide (LPS; 5 ng/kg BW), before carotid thrombosis was induced by photochemical injury. The translational value of these findings was investigated in primary human aortic endothelial cells (HAECs) and plasma samples of patients randomized to empagliflozin therapy. Results: The between-group difference in doppler-flow probe detected time-to-occlusion (TTO) remained within the predefined equivalence margin (Δ=|10.50|), irrespective of low-grade inflammation (95% confidence interval [CI], −9.82 to 8.85 and −9.20 to 9.69), while glucose dropped by 1.64 and 4.84 mmol/l, respectively (Fig. 1). Ex vivo platelet aggregometry suggests similar platelet activation status, corroborated by unchanged circulating platelet-factor 4 (PF4) plasma levels. In concert, carotid PAI-1 expression and TF activity remained unaltered upon SGLT-2 inhibition, and no difference in plasma D-dimer levels was detected, suggesting comparable coagulation cascade activation and fibrinolytic activity (Fig. 1). In HAECs pre-treated with LPS, empagliflozin neither changed TF activity nor PAI-1 expression (Fig. 2). Accordingly, among patients with established ASCVD or at high cardiovascular (CV) risk randomized to 10 mg empagliflozin daily signatures of thrombotic (i.e., TF) and fibrinolytic activity (i.e., PAI-1) remained unchanged, while plasma glucose declined significantly during 3 months of follow-up (Fig. 2). Conclusion: SGLT-2 inhibition by empagliflozin does not impact experimental arterial thrombus formation, neither under baseline conditions nor during sustained low-grade inflammation, and has no impact on proxies of thrombotic/fibrinolytic activity in patients with ASCVD. The beneficial pleiotropic effects of empagliflozin are likely independent of pathways mediating thrombosis. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swiss National Science FoundationSwiss Heart FoundationFoundation for Cardiovascular Research–Zurich Heart House